Immune checkpoint inhibitor-related pneumonitis in non-small cell lung cancer: A review - Hao, Yuxuan; Zhang, Xiaoye; Yu, Li (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have shown definite therapeutic effects in various types of cancers, especially non-small cell lung cancer (NSCLC). However, ICIs have unique side effects, called immune-related adverse events (irAEs), which can occur in various systems throughout the body. Among such irAEs, immune checkpoint inhibitor-related pneumonitis (ICI-P) is a fatal adverse reaction. In this review, we discussed the risk factors, pathogenesis, clinical characteristics, radiological manifestations, pathological features, diagnosis, grading, and management of ICI-P in NSCLC and the relationship between ICI-P and the efficacy of ICI therapy. In addition, we discussed the predictive factors for ICI-P. This review will play a crucial role in the prediction, evaluation, and management of ICI-P for widespread application of immunotherapy.